Response of People with Type 1 Diabetes for Follow Up - Sarfraz Ahmad Khan; Faiza Kamal; Rozina Arshad; Bilal Bin Younis; Rashid Ahmed (Shalamar Medical & Dental College, Lahore, Pakistan, 2019)
Diabetes is becoming a global epidemic. Type1 diabetes (T1DM) accounts for 3-5% of all the diabetics. As T1DM is diagnosed in childhood and adolescence, it is associated with more complications because of longer life span of individuals with this condition. The main objective of the study was to find out attitudes of people with type 1 diabetes especially with regards to their follow up. A cross-sectional study was planned and a total of 97 people with type 1 diabetes were included for a period of one year. To analyze the data SPSS 20.0 version was used. Results showed that out of 97 people, 48 (49.5%) were male and 49 (50.5%) were female. The mean age of total type 1 diabetics were 17.03±6.54 years. Mean glycated hemoglobin (HbA1c) was 10.59±3.09. The results revealed that 45% of people showed positive attitude and 55% showed negative behavior towards follow-up. It was concluded that overall follow up of people with type 1 diabetes was poor. It was observed that they wanted a complete cure and this contribute to missed follow up.